1994
DOI: 10.1007/bf01283030
|View full text |Cite
|
Sign up to set email alerts
|

Persistent psychosis after reduction in pre- and post-synaptic dopaminergic function

Abstract: The purpose of this study was to evaluate the hypothesis that neuroleptic non-response in the face of "adequate" DA post-synaptic receptor blockade reflects failure of regulatory mechanisms to decrease DA pre-synaptic activity. Eight chronic schizophrenics, meeting rigorous criteria for neuroleptic non-response, were treated for four weeks with alpha-methylparatyrosine as an adjunct to their previously stable neuroleptic dose. Treatment with AMPT produced a prompt decrease in plasma HVA that was, on average, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…10 Further support for the idea that treatment resistance is nondopaminergic comes from studies using drugs to deplete presynaptic dopamine stores. [11][12][13] These studies have found no benefit from dopamine depletion in treatment-resistant patients, in contrast to the reduction in psychotic symptoms that is seen in most patients.…”
Section: Introductionmentioning
confidence: 74%
“…10 Further support for the idea that treatment resistance is nondopaminergic comes from studies using drugs to deplete presynaptic dopamine stores. [11][12][13] These studies have found no benefit from dopamine depletion in treatment-resistant patients, in contrast to the reduction in psychotic symptoms that is seen in most patients.…”
Section: Introductionmentioning
confidence: 74%
“…However, approximately 30% show few or no gains from currently available treatments 4 . Data from dopamine depletion and positron emission tomography (PET) studies show that some individuals with refractory illness can have normal dopaminergic functioning 5 8 , which may explain their medication failure. Rather, a primarily glutamatergic dysfunction may be underpinning symptomatology, as evidenced by recent proton magnetic resonance spectroscopy (1H-MRS) studies that report elevated anterior cingulate cortex (ACC) glutamate levels in both first-episode and chronic illness individuals.…”
Section: Introductionmentioning
confidence: 99%